Organic residue analysis from five Neolithic and Eneolithic sites from eastern Croatia - Miloglav, Ina; Balen, Jacqueline (2012)
In the last few decades organic residue analysis become very important discipline in archaeology which help us to determinate and identify origins of organic remains in archaeological material, especially in ceramic sherds. Results of GC-MS analysis of pottery from five sites in eastern Croatia (Slavonija), belonging to Neolithic and Eneolithic period, shows that all the samples yield fatty acids and few of them contain residues of degraded beeswax. These results are compared and interpreted along with vessel form and its function and also with archaeological record of ceramic finds. Relationship between form and function of the vessel is one of the longest and most solid connections in the studies and analysis dealing with ceramic materials and organic residue analysis gives us the opportunity to take another step closer to reconstruct this ties. In this sense organic residue analysis represents a very challenging method which offers very interesting and perspective results to the archaeologists, especially in study of human activity in the past.
Projekt MZOS
ENG